Financial Ratio Analysis on Telecommunication Industry in Malaysia (Comparation between Maxis Berhad and Digi Berhad) - Yetti Tri Wulandari (University of Merdeka Malang, 2019)
This article analize financial ratio two leading telecommunication company in Malaysia Maxis Berhad and Digi Berhad. The analysis show Digi have better profitability ratios than Maxis Berhad. Efficiency ratio for both company is almost the same performance. Digi have higher leverage ratio and higher liquidity ratio. Maxis have better market ratio.